PENGGUNAAN KALIMAT IMPERATIF DALAM KOLOM KOMENTAR INSTAGRAM ERICK THOHIR DALAM POSTINGAN SEPAK BOLA DAN PSSI: KAJIAN SINTAKSIS - Ferdiansa, Deni (Universitas Hasanuddin, 2025)
This study aims to (1) determine the types imperative sentences in Erick Thohir's Instagram comments; (2) analyze and describe the meaning of the types of imperative sentences. The data source in this research from Erick Thohir's Instagram comment section five posts (highlight soccer and PSSI). The result of the research (1) the types of imperative sentences found are divided two types, (a) imperative sentences based on the content, five classes are obtained, namely 6 subtle imperative sentences, 3 imperative sentences of request, 5 imperative sentences of invitation and hope, 5 prohibition imperative sentences, and 3 warning imperative sentences. (b) imperative sentences based on their form, two types are obtained imperative sentences, namely nontransitive imperative sentences with predicate verbs and imperative sentences with markers that express wishes, prohibitions, order, and request. (2) The meanings formed from each type of imperative sentence are imperative sentences found are request, invitation, hope, prohibition, warning